2000
DOI: 10.1093/humrep/15.9.2008
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of severe twin-to-twin transfusion syndrome

Abstract: This extended series of 303 monochorionic twin pregnancies examined at 10-14 weeks gestation explores the possible association of increased fetal nuchal translucency thickness (NT) in the early prediction of severe twin-to-twin transfusion syndrome (TTS). Of 303 pregnancies, there were 16 in which at least one fetus was structurally or chromosomally abnormal and in the remaining 287 ongoing pregnancies there were 43 (15%) which developed severe TTS. The median fetal NT was 1.0 multiples of the median (MOM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
116
5
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(139 citation statements)
references
References 11 publications
8
116
5
10
Order By: Relevance
“…In chromosomally normal dichorionic twins, increased NT is likely to be due to an underlying mechanism similar to that in a singleton fetus, leading to a similar increased risk for adverse pregnancy outcome, although no specific data are available. However, in monochorionic twins, increased NT may also be produced by hemodynamic imbalances between the fetuses through the vascular anastomoses, which may result in severe early onset of TTTS 3,4 . Previous studies in singleton pregnancies have reported that an increased NT in a fetus with normal karyotype was associated with a poor pregnancy outcome, the chances of which increased exponentially with increasing NT thickness, from 8% when NT ranged between the 95 th and 99 th percentiles to 80-85% when the NT was above 6.5 mm 1,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chromosomally normal dichorionic twins, increased NT is likely to be due to an underlying mechanism similar to that in a singleton fetus, leading to a similar increased risk for adverse pregnancy outcome, although no specific data are available. However, in monochorionic twins, increased NT may also be produced by hemodynamic imbalances between the fetuses through the vascular anastomoses, which may result in severe early onset of TTTS 3,4 . Previous studies in singleton pregnancies have reported that an increased NT in a fetus with normal karyotype was associated with a poor pregnancy outcome, the chances of which increased exponentially with increasing NT thickness, from 8% when NT ranged between the 95 th and 99 th percentiles to 80-85% when the NT was above 6.5 mm 1,14 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this sign might constitute an early manifestation of TTTS 3,4 , but this notion has been questioned in more recent studies 5,6,22 . Therefore, it is suggested that this finding in a monochorionic twin should prompt a search for signs of TTTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin-to-twin transfusion syndrome (TTTS) occurs in about 15% of monochorionic twins, caused by imbalance in the net flow of blood between them across the placental communicating vessels [1,2]. The mortality rate of these twins exceeds 80%, and the risk of disability in the survivors is estimated to be 15-50% if untreated [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the content is in many ways commendable, the disregard of previous pivotal publications relating to the topic is disappointing. On Page 251, when the authors discuss the implications of discordance in nuchal translucency thickness (NT) and crown-rump length (CRL), they ignore the clinically relevant contribution of abnormal flow in the ductus venosus (DV) in screening for twin-to-twin transfusion syndrome (TTTS).We know from the papers of Sebire et al 2,3 that a higher prevalence of increased NT was noted among monochorionic (MC) twins along with a four-fold increase in the risk of developing TTTS in this subgroup. An intertwin difference in NT of more than 20% was a stronger marker for TTTS, but its sensitivity was unsatisfactory (around 50%) 4 .…”
mentioning
confidence: 99%